KAJI BANDING APLIKASI LIMBAH MEDIA TANAM JAMUR TIRAM DAN LIMBAH TAHU CAIR TERHADAP SIFAT KIMIA ANDISOL CANGAR, BATU - Farochatus Zakiyah; S Syekhfani; Retno Suntari (Jurnal Tanah dan Sumberdaya Lahan, 2015)
Industrial development grows rapidly nowadays, especially industries that support human life. In other side, every industry pays less attention for the system of disposing wastes such as oyster mushroom media waste and tofu liquid waste. This study was aimed to determine the effect of organic material application (oyster mushroom plant media waste and tofu liquid waste) through incubation toward availability of P, K, Ca, Mg, and Na in an Andisol of Cangar, Batu.Â  Treatments tested in this study were J1 (100% oyster mushroom compost), JC2 (75% oyster mushroom compost + 25% of tofu liquid waste), JC3 (50% oyster mushroom compost + 50% of tofu liquid waste), JC4 (25% oyster mushroom compost + 75% of tofu liquid waste), and C5 (100% of tofu liquid waste). The six treatments were arranged in a completely randomized design with three replicates. The results showed that application of 75% oyster mushroom compost + 25% tofu liquid waste (JC2) increased better soil K-availability and CEC until eighth-observations than the other treatments. Application ofÂ  50% oyster mushroom compost + 50% tofu liquid waste (C5) increased the amount of Mg-available from low criteria (0,56 mg/100g) into moderate criteria (1,30 mg/100g) compared with observation control.